Screening for primary aldosteronism in an argentinian population: a multicenter prospective study - Leal Reyna, Mariela (2015)
OBJECTIVES:Primary aldosteronism (PA) is characterized by the autonomous overproduction of aldosterone. Its prevalence has increased since the use of the aldosterone (ALD)/plasma renin activity (PRA) ratio (ARR). The objective of this study is to determine ARR and ARC (ALD/plasma renin concentration ratio) cut-off values (COV) and their diagnostic concordance (DC%) in the screening for PA in an Argentinian population.Design multicenter prospective study.SUBJECTS AND METHODS:We studied 353 subjects (104 controls and 249 hypertensive patients). Serum aldosterone, PRA and ARR were determined. In 220 randomly selected subjects, 160 hypertensive patients and 60 controls, plasma renin concentration (PRC) was simultaneously measured and ARC was determined.RESULTS:According to the 95th percentile of controls, we determined a COV of 36 for ARR and 2.39 for ARC, with ALD ≥ 15 ng/dL. In 31/249 hypertensive patients, ARR was ≥ 36. PA diagnosis was established in 8/31 patients (23/31 patients did not complete confirmatory tests). DC% between ARR and ARC was calculated. A significant correlation between ARR and ARC (r = 0.742; p < 0.0001) was found only with PRA > 0.3 ng/mL/h and PRC > 5 pg/mL. DC% for ARR and ARC above or below 36 and 2.39 was 79.1%, respectively.CONCLUSION:This first Argentinian multicenter study determined a COV of 36 for ARR and 2.39 for ARC. Applying an ARR ≥ 36 in the hypertensive group, we confirmed PA in a higher percentage of patients than the previously reported one in our population. As for ARC, further studies are needed for its clinical application, since DC% is acceptable only for medium range renin values.